Perfil, concepções e práticas pedagógicas de professores que atuam em turmas multisseriadas de escolas públicas de Sergipe - Parente, Cláudia da Mota Darós [UNESP] (FapUNIFESP (SciELO), 2014)
This article examines some aspects of the organization of multigrade schooling, taking as reference the state of Sergipe. It describes the profile, the conceptions and pedagogical practices of teachers working in multigrade classes in public schools. The data presented result from a statistical analysis of information collected by Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixiera (Inep) and from researches realized with public school teachers of Sergipe. The research has shown that the organization of multigrade schooling has different patterns and its central premise is the junction of years/grades, disregarding the age factor and inhibiting a possible pedagogical intervention, which considers the diversity of subjects and their lifetime. Therefore, it is necessary that teachers have a closer look at subjects of education in rural areas and build an educational intervention that goes beyond administrative aspects of formation of classes. The analysis of conceptions and practices of the teachers working in multigrade classes showed that the teaching work is obstructed by external determinations and by administrative barriers, inhibiting new reflections and practices that break up with the traditional logic of grades, permeated of excluding elements. The article aims to contribute to the dissemination of reflections and policies in the area of country education, especially for schools organized by multigrade schooling.

Analisa alguns aspectos da organização da escolarização em multisséries, tomando-se como referência o Estado de Sergipe e descrevendo o perfil, as concepções e as práticas pedagógicas de professores que atuam em turmas multisseriadas de escolas públicas. Os dados apresentados são decorrentes da análise estatística de informações disponibilizadas pelo Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (Inep) e de pesquisas realizadas com professores de escolas públicas de Sergipe. A pesquisa mostrou que a organização da escolarização em multisséries possui diferentes formas e tem como pressuposto central a junção de anos/séries, desconsiderando o elemento idade e inibindo uma possível intervenção pedagógica decorrente da diversidade de sujeitos e tempos de vida. Por isso, é preciso que os professores tenham um olhar mais atento aos sujeitos do campo e construam uma intervenção pedagógica que ultrapasse os aspectos administrativos de enturmação. A análise das concepções e das práticas de professores que atuam em turmas multisseriadas evidenciou que o trabalho docente está engessado por determinações externas e por barreiras administrativas, inibindo novas reflexões e práticas que rompam com as lógicas tradicionais da seriação, permeadas de elementos excludentes. O artigo pretende contribuir para a disseminação de reflexões e políticas na área da educação do campo, sobretudo em escolas que possuem organização da escolarização em multisséries.